Effekter av transport och buller på grisars aktivitet samt aggressiva interaktioner i väntan på slakt - Stålhandske, Linnéa (SLU/Dept. of Animal Environment and Health (until 231231), 2005)
During pre-slaughter handling of pigs the animals are often subjected to methods that induces stress and are a threat to the wellbeing of the animals, such as mixing of groups, loud noise and transportation. A new law will be implemented in 2006 in Sweden that prohibits mechanical noise exceeding 65 dB in abattoirs. The purpose of the research presented in this paper was to examine the effects of noise and transportation on pig behaviour. The activity and aggressiveness of the pigs were examined with behavioural studies during transportation and during three different noise levels: 55, 75 and 95 dB. Before the noise treatments took place the groups were mixed and half of them were transported for approximately 2 hours. In the study 432 pigs were used. Everyday 24 pigs were used, and divided into two groups, with 12 in each. Therefore two different pens were used, both during transportation and lairage. During transportation the pens were of different sizes giving different densities. In the lairage there were also differences in the pens, one of the boxes consisting of three walls and one gate (pen 1) and the other of two walls and two gates (pen 2). Three different behavioural observations took place; one during transport and two during waiting in the lairage. The animals were videotaped so that the aggressive encounters could be examined in detail. Focus was made on the characters of the attacks and the interactions but also the number of individuals participating in aggressive encounters and in which way. During transportation the pigs were active 91,3% of the time. The pigs sat down significantly more in the smaller pen with higher density. The transportation also affected the behaviour of the pigs during lairage. Pigs that had been subjected to transportation laid less often on their side and more often on their stomach than pigs not subjected to transportation. They also fought less and spent more time in oral contact with other pigs. The characters of the encounters were also affected; the frequency of passive interactions and harassment became lower after transportation. In respond to this a theory can be formed that the transportation is energy demanding for the pigs and leads to exhaustion. Transportation did not lower the level of aggression since the attack forms and the characters of the encounters were not affected. The different placing of the two pens in the lairage led to the pig standing up and walking significantly more in pen 2 regardless the treatment. Pigs subjected to transportation also stood and walked more in pen 2 than in pen 1. Transported pigs laid more often on the stomach in pen 1 than in pen 2. Therefore a conclusion is made that pen 1 gives the pigs a more safe and stable environment. During the research 80% of the pigs participated in aggressive interactions and 54, 2% were active aggressive by attacking others. The results show a change in the attack form when subjected to loud noise. Attacks in head to head position and parallel position were less common during treatments with 95 dB. The total number of attacks was not affected. The characteristics of the interactions also changed in treatments with 95 dB. Passive aggression and harassment occurred less often, but the total amount of aggressive interactions was not affected. A theory is based upon these results that loud noise decreases the possibilities for the pigs to communicate. Both noise and transportation can be a threat to the wellbeing of the pigs. As a conclusion more studies has to be done in detail on the behaviour of pigs when subjected to noise and transportation, to elucidate the exact effects.